Stabilization and dewatering of wastewater treatment plants sludge using the Fenton process - Abolfazl Azhdarpoor; Zahra Mohammadi; Mansoureh Dehghani (Iranian Journal of Health, Safety and Environment, 2015)
Wastewater sludge typically contains large amounts of water and organic materials; therefore, its stabilization and dewatering is of particular importance. In this study, Fenton oxidation process is used for stabilization and dewatering of sludge in the output of a wastewater treatment plant. To evaluate the sludge stabilization and dewatering, specific resistance to filtration (SRF), volatile organic compounds (VSS), total suspended solids (TSS), soluble chemical oxygen demand (SCOD) and heterotrophic bacteria were measured. During the experiment, the optimal values of various parameters such as pH (2-9), hydrogen peroxide (0.015- 0.18mol/L), Fe2+ (0.008- 0.1mol/L) and time (5 - 60 minutes) for optimum sludge dewatering and stabilization were investigated. The results showed that the highest percentages of SRF reduction and removal rates of SCOD, VSS and TSS were 99.48, 61, 42, and 41 percent respectively. These results were obtained in optimum pH 5, 0.05 mol/l Fe2+, 0.12 mol/l hydrogen peroxide, and the retention time of 15 minutes. The removal rate of heterotrophic bacteria increased with increasing dose of hydrogen peroxide, so that a removal rate of 84 percent was observed at a dose of 0.18 mol/l. In general, Fenton process can reduce volatile organic materials and chemical oxygen demand of the sludge resulting in its significant stabilization and dewatering. In general, Fenton process can reduce volatile organic materials and chemical oxygen demand of the sludge resulting in its significant stabilization and dewatering.